2007
DOI: 10.1038/emm.2007.16
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reduces cold storage-induced damage in human cardiac myoblasts

Abstract: Curcumin is a polyphenolic compound possessing interesting anti-inflammatory and antioxidant properties and has the ability to induce the defensive protein heme oxygenase-1 (HO-1). The objective of this study was to investigate whether curcumin protects against cold storage-mediated damage of human adult atrial myoblast cells (Girardi cells) and to assess the potential involvement of HO-1 in this process. Girardi cells were exposed to either normothermic or hypothermic conditions in Celsior preservation soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Both biliverdin and bilirubin possess antioxidant properties (28). Ample evidence supports the notion that up-regulation of heme oxygenase-1 expression provides potent cytoprotective effects in many in vitro and in vivo models of oxidative stress-induced cellular and tissue injury (15,19,(28)(29)(30). Many recent studies have revealed that curcumin potently induces heme oxygenase-1 expression, such as in cardiac myoblasts (29), hepatocytes (30), and monocytes (28), leading to increased resistance to oxidative stress-mediated damage.…”
Section: Discussionmentioning
confidence: 94%
“…Both biliverdin and bilirubin possess antioxidant properties (28). Ample evidence supports the notion that up-regulation of heme oxygenase-1 expression provides potent cytoprotective effects in many in vitro and in vivo models of oxidative stress-induced cellular and tissue injury (15,19,(28)(29)(30). Many recent studies have revealed that curcumin potently induces heme oxygenase-1 expression, such as in cardiac myoblasts (29), hepatocytes (30), and monocytes (28), leading to increased resistance to oxidative stress-mediated damage.…”
Section: Discussionmentioning
confidence: 94%
“…2-4). In particular, curcumin increased the expression of HO-1 in human cardiac myoblasts, hepatocytes, monocytes and endothelial cells, rat neurons and astrocytes as well as porcine endothelial cells [34, [146][147][148][149][150]. In rodents and human cells, curcumin-induced HO-1 overexpression was correlated with production of mitochondrial ROS, activation of transcription factors Nrf2 and NF-jB, induction of MAPK p38 and inhibition of phosphatase activity [149,151,152].…”
Section: Natural Antioxidants Vitagenes and Neurodegenerative Disordersmentioning
confidence: 99%
“…Similarly to sulforaphane, in addition to potently inducing cytoprotective proteins, curcumin is a pleiotropic agent with multiple molecular targets and biological activities (reviewed in [96][97][98]). Interestingly, because of its cytoprotective effects (that have been attributed largely to induction of HO-1) against damage induced by cold preservation/warm reperfusion in cultured renal epithelial cells [99], hepatocytes [100], and cardiac myoblasts [101], a potential clinical use of curcumin has been suggested in the processes related to organ storage and transplantation.…”
Section: Michael Acceptors a Prominent Class Of Inducers Of Cytoprotmentioning
confidence: 99%